Longitudinal changes in bone mineral density in children with inflammatory bowel diseases. (27th October 2019) - Levy‐Shraga, Yael; Shenkar, Anatoly; Modan‐Moses, Dalit; Assa, Amit; Haberman, Yael; Shouval, Dror; Guz‐Mark, Anat; Lahad, Avishay; Weiss, Batia
Abstract: Aim: Children with inflammatory bowel disease (IBD) are prone to low bone mineral density (BMD). Our aim was to assess longitudinal changes in BMD in this population. Methods: A retrospective longitudinal study of children with IBD, treated at two tertiary centres in Israel, who underwent two BMD measurements by dual‐energy X‐ray absorptiometry (DXA). Changes in lumbar spine BMD (∆L1‐4 z‐scores) were examined for correlations with clinical characteristics. Results: The cohort included 41 patients (age at diagnosis 12.1 ± 3.5 years, 23 females).The mean interval between the scans was 3.4 ± 2.0 years. There was a trend towards improvement in L1‐4 z‐scores (−1.64 ± 1.02 vs −1.45 ± 0.83, P  = .12). ∆L1‐4 z‐scores correlated positively with ∆weight‐standard deviation scores (SDS), ∆height‐SDS and ∆BMI‐SDS, and with age at the second scan ( R  = .55, P  < .01; R  = .42, P  < .01; R  = .42, P  = .01; R  = .35, P  = .02, respectively); and negatively with L1‐4 z‐scores at the first scan ( R  = −.63, P  < .01). Stepwise linear regression analysis identified the first scan L1‐4 z‐scores and ∆weight‐SDS as independent predictors of ∆L1‐4 z‐scores. An L1‐4 z‐score ≤−2 at the first DXA scan was associated with significant improvement at the second scan. Conclusion: Improvement in BMD was more pronounced in children who gained weight or whose BMD was low at the first scan.